The effect of profitability, financial leverage and growth opportunities on dividend policy with firm size as moderation - Gita Genia Fatihat,; Reva Yuliani,; Eristy Minda Utami, (Technium Social Sciences Journal, 2025)
The purpose of this research is to determine the effect of profitability, financial leverage, and growth opportunities on dividend policy with firm size as a moderator. The methodology of this research is panel data regression. The sampling technique used is purposive sampling. The sample used consists of companies engaged in the manufacturing sector listed on the LQ45 Index of the Indonesia Stock Exchange from 2019 to 2023. The conclusion of this research is that profitability has a significant impact on dividend policy, while financial leverage and growth opportunities do not have a significant impact on dividend policy. This is because larger companies will have greater profits, which will impact the payment of dividends to shareholders. The second conclusion is that firm size moderates the influence of profitability on dividend policy, while financial leverage and growth opportunities are not significant to dividend policy.